Three Types of Transnational Players: differing women’s football mobility projects in core and developing countries - Tiesler, Nina Clara, 1968- (2014)
Mobile players in men’s football are highly skilled professionals who move to a country other than the one where they grew up and started their careers. They are commonly described as migrants or expatriate players. Due to a much less advanced stage of professionalism and production of the game in women’s football mobility projects are different. The percentage of cases which drop out of these concepts developed for men’s football migration increases when specifically looking at the peripheral and semi-peripheral countries. At describing the cases of Brazil, Equatorial Guinea, Mexico, Colombia and Portugal, the aim of this paper is to conceptualise an umbrella category for mobile players that can include current realities in the women’s game, namely the transnational player who has gained and displays transnational football experience in different countries and socio-culturally contexts. Analysis is based on original data on fluxes, 31 interviews with mobile players from diverse countries and secondary data material on players’ biographies. It allows pointing out some main features of the increasing international mobility of women footballers and suggests that players who are crossing borders impact significantly on the development of the game at global scale.